Current insights into transcriptional role(s) for the nutraceutical Withania somnifera in inflammation and aging - Saha, Praful; Ajgaonkar, Saiprasad; Maniar, Dishant; Sahare, Simran; Mehta, Dilip; Nair, Sujit (Frontiers in Nutrition, 2024)
The health-beneficial effects of nutraceuticals in various diseases have received enhanced attention in recent years. Aging is a continuous process wherein physiological activity of an individual declines over time and is characterized by various indefinite hallmarks which contribute toward aging-related comorbidities in an individual which include many neurodegenerative diseases, cardiac problems, diabetes, bone-degeneration, and cancer. Cellular senescence is a homeostatic biological process that has an important function in driving aging. Currently, a growing body of evidence substantiates the connection between epigenetic modifications and the aging process, along with aging-related diseases. These modifications are now being recognized as promising targets for emerging therapeutic interventions. Considering that almost all the biological processes are modulated by RNAs, numerous RNA-binding proteins have been found to be linked to aging and age-related complexities. Currently, studies have shed light on the ability of the nutraceutical Withania somnifera (Ashwagandha) to influence RNA expression, stability, and processing, offering insights into its mechanisms of action. By targeting RNA-related pathways, Withania somnifera may exhibit promising effects in ameliorating age-associated molecular changes, which include modifications in gene expression and signaling networks. This review summarizes the potential role of Withania somnifera as a nutraceutical in modulating RNA-level changes associated with aging, encompassing both in vitro and in vivo studies. Taken together, the putative role(s) of Withania in modulation of key RNAs will provide insights into understanding the aging process and facilitate the development of various preventive and therapeutic strategies employing nutraceuticals for healthy aging.